Smart Graphics 11th International Symposium, SG 2011, Bremen, Germany, July 18-20, 2011. Proceedings - Dickmann, Lutz.; Volkmann, Gerald; Malaka, Rainer; Boll, Susanne; Krüger, Antonio; Olivier, Patrick; SpringerLink (Online service). (aBerlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 11th International Symposium on Smart Graphics, SG 2011, held in Bremen, Germany, in July 2011. The 10 revised full papers presented together with 12 short papers and 4 systems demonstrations were carefully reviewed and selected from numerous submissions covering a wide range of topics including view and camera control; three-dimensional modeling; visual information encoding;video projection; information visualization; interaction techniques; visual communication; and graphics and audio.
Electronic reproduction.
Keywords: Computer graphics -- Congresses; Electronic books